Harassment in Academic Medicine: One Hundred Years of Solitude - Abdulla, Ebtesam; Agrawal, Amit; Cincu, Rafael; Janjua, Tariq; Moscote-Salazar, Luis Rafael (Nepal Journal of Neuroscience, 2023)
There are dozens of cases of harassment and bullying in academic medicine that are hidden in the most hidden drawers. Harassment in academic medicine is an accepted and widely recognized problem. As a common pattern, the protagonists are always someone with power against people with a lower hierarchy. Abuse in any of its forms, be it physical, moral, or academic, ends up affecting the student’s performance and behavior. It should be considered an unacceptable and punishable pattern in any academic setting.